PENGARUH TERPAAN KONTEN TIKTOK HALIMAH (@DAILYJOUR) TERHADAP PEMENUHAN KEBUTUHAN INFORMASI PENGASUHAN ANAK FOLLOWERS - Dwi Gustina Purnama Sari; Nurjanah (PROGRAM STUDI ILMU KOMUNIKASI, 2023)
Tiktok is one of the social media that currently widely used by the public which allows users to share short-duration vertical videos from 15 seconds to 10 minutes. There are variations of content to expose and fulfill the public's information needs on tiktok, one of which is content by Halimah (@dailyjour). This research aims to measure the effect of Halimah (@dailyjour) TikTok’s content exposure to fulfill the followers' parenting information needs. Samples were taken by reaching out to 400 respondents based on the opportunity found on Halimah (@dailyjour)’s Tiktok Account (accidental sampling). Based on the result of this research, the simple linear regression result shows that t value 19,436 > t table 1,966, which means there is an effect of Halimah (@dailyjour) TikTok account’s content exposure to fulfill the followers' parenting information needs. The coefficient determination test shows the R Square value is 0,487. The value of the coefficient determination (R Square) means that the effect of Halimah (@dailyjour) TikTok account’s content exposure to fulfill the followers' parenting information needs is 48,7% and categorized as a moderate effect. Therefore, the results of the research show that Ho is rejected and Ha is accepted.